EVALUASI POSTUR KERJA DI STASIUN KERJA CRIMPING SPLICE PT. XXX DENGAN METODE QUICK EXPOSURE CHECK - Purbasari, Annisa; Alex, Mr.; H. Siboro, Benedikta Anna (SIGMA TEKNIKA, 2020)
Work posture at the crimping splice work station at line lamp 1 PT. XXX shows that there is dominant work done in static work positions, repetitive and monotonous work. The work posture that occurs during the process shows the work position of the operator sitting forward for a long time for 1 working day (8 hours) using a work chair without a backrest. This research aims to analyze and evaluate of operators work posture error on the production process in electronic manufacturing industry. Subject data retrieval for 15 operators. This work station consists of 15 processes that are all done in a sitting position. The work risk assessment uses the Quick Exposure Check (QEC) method. The results showed in the process of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 at the crimping splice work station, posture of workers who are likely to have a very high working risk felt pain on the back part. The whole process at the crimping splice work station shows the work posture of workers who have a very high work risk feel pain in the neck. The exposure level value in this study shows that all processes in the crimping splice work station are in the range of 59.88% -71.60% so that each process in the crimping splice work station is categorized to be done change as soon as possible.